Application of Objective Structured Clinical Examination in orientation training of night shift among newly recruited nurses (客观结构化临床考试在新入科护士夜班准入培训中的应用) - ZENG Jinyuan (曾金园); LUO Yu (罗玉); GUO Cuiwen (郭翠文); CHEN Liushan (陈柳珊) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of Objective Structured Clinical Examination (OSCE) in orientation training of night shift among newly recruited nurses. Methods Totally 26 registered nurses who required orientation training of night shift were divided into the observation group and control group. Routine theory and practice tests were carried out in the control group, and OSCE was performed in the observation group. The nurse's satisfaction with training, comprehensive skills assessment outcome and exam result were observed and compared between two groups. Results The satisfaction rate of observation group was higher than that of control group (P＜0. 05). The scores of comprehensive skills assessment and theory test in the observation group were higher than those in the control group (P＜0. 05). Conclusion The OSCE in orientation training of night shift is potentially effective to enhance the comprehensive skills of nurses and improve their satisfaction. (目的 探讨客观结构化临床考试(OSCE)在新入科夜班护士准入培训中的应用效果。方法 26名注册护士分为观察组和对照组, 参加夜班准入培训。对照组护士采用常规理论及单项操作考试, 观察组采用OSCE。比较2组护士对培训的满意度、综合能力得分以及考试成绩。结果 观察组对培训效果的满意度高于对照组 (P＜0. 05)。观察组综合能力评分和考试成绩得分均高于对照组, 差异有统计学意义(P＜0. 05)。结论 OSCE应用于新入科夜班护士准入培训, 能有效提高其临床综合能力, 护士对该培训方式满意度较高。)